Influência da solução irrigadora e do material obturador na infiltração apical de dentes tratados endodonticamente : avaliação pelo método de filtração de fluidos - Candeiro, George Táccio de Miranda (2010)
One of the aims of endodontic treatment is to promote the repair in the periapical region, from technical procedures including chemomechanical preparation, represented by the instrumentation associated to irrigation and aspiration, in addition to filling the root canal system. Thus, in Endodontics several irrigation solutions have been employed with the main functions of dentin walls lubrication, organic matter dissolution, removal of microorganisms and smear layer removal. Sodium hypochlorite is the most used substance, however, it possesses some disadvantages, such as high tissue toxicity. Others irrigation solution alternatives have been proposed, such as chlorhexidine and apple vinegar, which has suitable biocompatibility and ability to remove the smear layer. The root canal filling presents technical objectives, focused on the full sealing of the root canal system, as well as, biological, enabling closure of the apical foramen, through the deposition of mineralized tissue. For many years, gutta-percha associated with a sealer has been used, however, with the advent of adhesive materials in dental clinic, some hit the market with employment in Endodontics, the most known Resilon/Epiphany system. Thus, the objective of this study was to assess, by fluid filtration method, the influence of irrigation solution and the filling materials (cones and sealer) association in the apical root leakage. One hundred twelve lower pre-molars human teeth were instrumented and filled, being initially divided into two controls groups and 8 groups (n = 12), according to the irrigation solution, (H) sodium hypochlorite, (V) apple vinegar, and root canal filling materials, gutta-percha/AH Plus (GA), Resilon/Epiphany (RE), gutta-percha/Epiphany (GE) and Resilon/AH Plus (RA). The results have showed no statistical difference in relation to the irrigation solutions used (p> 0.05), nevertheless, it was found that the groups filled with Resilon/AH Plus (H/RA and V/RA) association had significantly more leakage than the other groups (p <0.05). It was concluded that the apical leakage were influenced only by the filling material regardless the irrigation solution.